Case fatality and functional outcome after spontaneous subarachnoid haemorrhage: a systematic review and meta-analysis of time trends and regional variations in population-based studies - Ziebart, Andreas; Dremel, Judith; Hetjens, Svetlana; Nieuwkamp, Dennis J.; Linn, Francisca H. H.; Etminan, Nima; Rinkel, Gabriel J. E. (European stroke journal, 2024)
Introduction: A previous systematic review of population-based studies from 1973 to 2002 found a decrease in case fatality for spontaneous subarachnoid haemorrhage, but could not find a sufficient number of studies to assess changes in functional outcome. Since then, treatment has advanced distinctly. We assessed whether case fatality has decreased further and whether functional outcome has improved. - Patients and methods: We searched PubMed and Web of Science for new population-based studies using the same criteria as in our previous systematic review. We assessed changes in case fatality and functional outcome over time using linear regression. - Results: We included 24 new studies with 827 patients and analysed 9542 patients described in 62 study periods between 1973 and 2017. Case fatality decreased by 0.3% (95% CI: −0.7 to 0.1) per year. In a sensitivity analysis excluding studies that did not provide 1-month outcome and outliers, the age and sex-adjusted decrease was 0.1% per year (95% CI: −0.9 to 0.6). The mean case fatality rate decreased from 47% (95% CI: 31-63) in the 1970s to 35% (95% CI: 30-39) in the 1990s, and remained stable in the 2000s (34%; 95% CI: 27-41) and 2010s (38%; 95% CI: 15-60). In 15 studies, the mean proportion of patients living independently increased by 0.2% per year (95%CI: −0.7 to 1.1) and the mean was 45% (95% CI: 39-50) in six studies that reported outcome after 12 months. - Discussion and conclusion: From 1973 to 2017, the case-fatality rate of spontaneous subarachnoid haemorrhage declined overall by 13.5%, but remained stable over the last two decades. The data on time trends in functional outcome were inconclusive.
Gesehen am 09.09.2024